Assessment of the Global Fund-supported procurement and supply chain reforms at the Ethiopian Pharmaceuticals Supply Agency: a mixed-methods study - Sunil Garg; Patrick Githendu; Linden Morrison; Abaleng Lesego; Tom Achoki; Tsion Tsegaye; Lawrence P.O. Were; George Sakvarelidze; Solomon Nigussie (BMJ Open)
Objective The Global Fund to Fight AIDS, Tuberculosis and Malaria (Global Fund) partnered with the Ethiopian Pharmaceutical Supply Agency (EPSA) in 2018–2019 to reform procurement and supply chain management (PSCM) procedures within the Ethiopian healthcare system. This assessment sought to determine the impact of the reforms and document the lessons learnt.Design Mixed-methods study incorporating qualitative and quantitative analysis. Purposive and snowballing sampling techniques were applied for the qualitative methods, and the data collected was transcribed in full and subjected to thematic content analysis. Descriptive analysis was applied to quantitative data.Setting The study was based in Ethiopia and focused on the EPSA operations nationally between 2017 and 2021.Participants Twenty-five Ethiopian healthcare decision-makers and health workers.Intervention Global Fund training programme for health workers and infrastructural improvementsOutcomes Operational and financial measures for healthcare PSCM.Results The availability of antiretrovirals, tuberculosis and malaria medicines, and other related commodities, remained consistently high. Line fill rate and forecast accuracy were average. Between 2018 and 2021, procurement lead times for HIV and malaria-related orders reduced by 43.0% relative to other commodities that reported an increase. Many interview respondents recognised the important role of the Global Fund support in improving the performance of EPSA and provided specific attributions to the observed successes. However, they were also clear that more needs to be done in specific critical areas such as financing, strategic reorganisation, data and information management systems.Conclusion The Global Fund-supported initiatives led to improvements in the EPSA performance, despite several persistent challenges. To sustain and secure the gains achieved so far through Global Fund support and make progress, it is important that various stakeholders, including the government and the donor community, work together to support EPSA in delivering on its core mandate within the Ethiopian health system.